Decreased grip strength, muscle pain, and atrophy occur in rats following long‐term exposure to excessive repetitive motion. Issue 11 (16th October 2017) - Fujiwara, Mitsuhiro; Iwata, Masahiro; Inoue, Takayuki; Aizawa, Yosuke; Yoshito, Natsumi; Hayashi, Kazuhiro; Suzuki, Shigeyuki
Abstract : Work‐related musculoskeletal disorders (WMSD) are caused by the overuse of muscles in the workplace. Performing repetitive tasks is a primary risk factor for the development of WMSD. Many workers in highly repetitive jobs exhibit muscle pain and decline in handgrip strength, yet the mechanisms underlying these dysfunctions are poorly understood. In our study, rats performed voluntary repetitive reaching and grasping tasks (Task group), while Control group rats did not perform these activities. In the Task group, grip strength and forearm flexor withdrawal threshold declined significantly from week 2 to week 6, compared with these values at week 0 ( P < 0.05). Relative muscle weight and muscle fiber cross‐sectional area of flexor digitorum superficialis (FDS) muscles decreased significantly in the Task group, compared with the Control group, at 6 weeks ( P < 0.05 and P < 0.01, respectively). Nerve growth factor, glial cell line‐derived neurotrophic factor, and tumor necrosis factor α‐expression in FDS muscles were not significantly different in Control and Task groups at 3 and 6 weeks. At 6 weeks, the Task group had elevated MuRF1 protein levels ( P = 0.065) and significant overexpression of the autophagy‐related (Atg) proteins, Beclin1 and Atg5–Atg12, compared with in the Control group (both P < 0.05). These data suggested that long‐term exposure to excessive repetitive motion causes loss of grip strength, muscle pain, and skeletal muscle atrophy. Furthermore, this exposure may enhance protein degradation through both the ubiquitin‐proteasome and autophagy‐lysosome systems, thereby decreasing skeletal muscle mass. Abstract : Performing repetitive tasks is a primary risk factor for the development of work‐related musculoskeletal disorders. In our study, rats performed voluntary repetitive reaching and grasping tasks. We found that long‐term exposure to excessive repetitive motion causes the loss of grip strength, muscle pain, and skeletal muscle atrophy. Furthermore, this exposure may enhance protein degradation through both the ubiquitin‐proteasome and autophagy‐lysosome systems.